Serum Folate, Vitamin B12 Levels, and Systemic Immune-Inflammation Index Correlate With Motor Performance in Parkinson's Disease: A Cross-Sectional Study - Li, Siying; Zhang, Qingxi; Gao, Yuyuan; Nie, Kun; Liang, Yanling; Zhang, Yuhu; Wang, Lijuan (Frontiers in Neurology, 2021)
This study aimed to investigate the influence of serum folate, vitamin B12 (VitB12) levels, and inflammation-based scores on the motor performance status in Parkinson's disease (PD). We retrospectively collected data from 148 consecutive patients with idiopathic PD first admitted to our hospital. We measured whole blood count, albumin, lactate dehydrogenase, C-reactive protein, folate, and VitB12 levels and calculated the inflammation-based scores. The following scales were applied to assess the motor performance status: activity of daily living scale (ADL, the Barthel Index), the Unified Parkinson's Disease Rating Scale Part III (UPDRS-III), and Hoehn–Yahr (H–Y) classification. The geometric mean of folate and VitB12 levels were 11.87 (ng/ml) and 330.52 (pmol/L), respectively. Folate deficiency (serum level < 4.0 ng/ml) and VitB12 deficiency (serum level < 133 pg/ml) were present in 0.7 and 5.4% of the patients, respectively. The mean prognostic nutritional index (PNI) and systemic immune-inflammation index (SII) were 47.78 ± 4.42 and 470.81 ± 254.05, respectively. The multivariate analyses showed that serum VitB12 level (P = 0.002) and SII (P = 0.005) were significant factors for ADL score; serum folate (P = 0.027) and VitB12 (P = 0.037) levels for UPDRS-III score; and serum folate (P = 0.066) and VitB12 (P = 0.017) levels for H–Y classification. The elevated folate level did correlate with greater decline in UPDRS-III score (P = 0.023) and H–Y classification (P = 0.003), whereas there was an obvious increase in ADL score (P = 0.048). SII was negatively associated (P < 0.001) with the ADL score. The three-dimensional drawing, combined with the effect of folate and VitB12 levels, showed that the lowest level of folate was associated with the lowest ADL score and the highest UPDRS-III score and H–Y classification. This study indicates that serum folate, VitB12 levels, and SII are significant factors influencing the motor performance status in patients with PD. SII is negatively associated with ADL. Elevated serum folate level correlates with mild motor impairment in patients with PD.